Victor Grant Collection, Album 5, Photograph 280 A. C. Hoover Blacksmith shop
Handwriting on the back of the photograph reads: "A. C. Hoover in his Blacksmith Shop. A pioneer blacksmith of the early mining and cattle days in the Cimarron Country."
Designation 5.280 in listing stands for Album 5, Photograph 280.
From collection of photographs compiled by Victor Grant, descendant of the Maxwell / Beaubien family.
Located in Office Closet
Keywords: Hoover, A. C; New Mexico -- Genealogy - Photographic collection